Pemberian Arang Aktif Dari Cangkang Kelapa Sawit Terhadap Penyerapan Logam Berat Kadmium (Cd) Dan Tembaga (Cu) Pada Air Asam Tambang - Irwansyah Noor; Bambang Joko Priatmadi; Fatmawati Fatmawati; Kissinger Kissinger (Universitas Lambung Mangkurat, 2020)
One of the solutions for solving the acid mine drainage problem of heavy metal like cadmium (Cd) and cooper (Cu) is by using activated charcoal from palm oil shell and activating H3PO4 to enlarge pores of charcoal surface, then it can adsorp maximum amount of heavy metal. The purposes of this research are for analyzing the characteristic of activated charcoal from palm oil shell by activating H3PO4, analyzing the effect of applicated charcoal with or without activating H3PO4 for heavy metal like Cd, Cu and pH in acid mine drainage, and analyzing the variations of the most effective dose of heavy metal adsorption like Cd, Cu and pH enhancement. This research using the experiment method for testing the ability of activated charcoal from palm oil shell for cadmium (Cd) and cooper (Cu) heavy metal adsorption in acid mine drainage using Completely Randomized Design Non Factorial using one factor of treatment and difference of activated charcoal doses are 5 g, 10 g, 20 g dan 30 g with three times of repetitions. The result of this research showing that the characteristic of charcoal from palm oil shell can be used as an ingredient for making the activated charcoal that fulfill the quality of activated charcoal accordance with the standart of SNI 06-3730-95, the application of activated charcoal from palm oil shell by activating H3PO4 which iseffected for Cd and Cu heavy metal and pH of acid mine drainage, the application of activated charcoal from palm oil shell with or without activating H3PO4 is effected for pH of acid mine drainage with a little difference that activated charcoal has better result than the unactivated charcoal, and the most effective dose of variations of activated charcoal by using H3PO4 is 5 g for adsorpting Cd and Cu and the most effective dose for enhancing pH is 30 g.